How Transitions in Dementia Care Trajectories Affect Health Problems in Partners: A Longitudinal Analysis With Linked Health and Administrative Data. (29th November 2020) - van der Heide, Iris; Heins, Marianne J; van Hout, Hein P J; Verheij, Robert A; Francke, Anneke L; Joling, Karlijn J
Abstract: Objectives: To evaluate whether the prevalence of health problems in cohabiting partners of people with dementia differs between the year before and the year after 3 transitions: the diagnosis of dementia, institutionalization, and the death of the person with dementia. Methods: Individuals with dementia and their partners were identified on the basis of data in the electronic health records (EHRs) of 451 Dutch general practices. EHRs were also the data source on their health problems, which were linked to the Dutch population registry and health administration data with demographic characteristics, date of institutionalization, and date of death. Differences in the prevalence of 16 groups of health problems and of specific health problems in partners during the year before and the year after the 3 transitions were examined using a generalized estimating equation. Results: About 1, 110 partners of persons with dementia were identified. Problems related to the illness and/or loss of the person with dementia were significantly more prevalent in the year after the dementia diagnosis (32% vs. 17%) and in the year after the death of the person with dementia (59% vs. 41%) than in the years before. Unspecified health problems were more prevalent in the year after the diagnosis than in the year before (30% vs. 22%). After institutionalization, an increase was found in digestive problems and urological problems (30% vs. 18% and 24% vs. 17%). Discussion: Transitions during the dementia care trajectory, namely, the diagnosis, institutionalization, and death of the person with dementia, significantly affect the cohabiting partner's health.